Financial Decisions and Investment Outcomes in Developing Countries : The Role of Institutions - Turk, Rima (IMF Working Papers; Working Paper ;, 2015)
This paper analyzes how differences in legal origin, judicial efficiency, and investor protection affect firm leverage and earnings volatility across developing countries. Using a large number of developing countries, four main findings are highlighted. First, firms in civil legal origin countries rely more on debt financing compared to firms in common law countries, and they exhibit lower earnings volatility. Second, under weak judicial enforcement, firms tend to borrow more but they take less risk. Third, stronger creditor rights increase debt financing and reduce earnings volatility. Fourth, firm listing on a developed stock exchange shifts the capital structure towards more equity financing, and it increases the firm's ability to borrow more when the judicial system is inefficient. The results reinforce the importance of strengthening laws and institutions as well as deepening capital markets in developing countries to improve financing conditions and investment outcomes.